PENYULUHAN CTPS SEBAGAI UPAYA PENCEGAHAN STUNTING PADA SISWA-SISWI RA HUSNUL KHOTIMAH - Permatasari, Rinda Lailia; MULYANI , LEDISTIA; Noviani, Dina; Rahmat, Delli Yuliana (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
One of the causes of stunting is the lack of practicing clean and healthy living and washing hands with soap, which has an impact on disease transmission. This affects the child’s appetite and causing a loss of essential nutrients for growth. The activity’s goal is to develop the childrens at RA Husnul Khotimah understanding of living hygienically and healthily by washing their hands. The activity’s method is counseling, demonstrations using video and the implementation of pre and posttest. The target taken were 46 RA Husnul Khotimah students using cluster random sampling technique. The outcomes of the counseling activities demostrated that the knowledge level was 41.3% (Enough) prior to counseling and increased by 10.9% with a posttest result of 52.2% (Good). The conclusion shows that there is an improvement in knowledge in early childhood in RA Husnul Khotimah.